The Development of P5 E-Module Based on the Pancasila Character of Primary School Students - Widiyanto, Rohmat; Ahmariyah, Fathimah Syafaqul (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to develop an electronic module project strengthening the Pancasila student profile that is valid and practical for grade IV students of SDI Ar-Riyadh Insan Cendekia, using the reasearch and development (R&D) method and the ADDIE development model which has five stages in developing it, namely the analysis, design, development, implementation, and evaluation stages. The results showed that the e-module developed based on the material expert validator obtained 91.25%, the media expert obtained 90%, the linguist obtained 86%, so that the researcher's e-module product was declared valid. The field practitioner by the teacher obtained 98.75%, and the results of the limited student product trial questionnaire obtained 92.5%, while the results of the free student product trial questionnaire obtained 95.25%, so that the e-module was declared very practical. Based on the results of this study, the e-module product that the researchers developed was declared valid and very practical. Thus, the e-module product of the project to strengthen the profile of Pancasila students for phase B can be used for learning materials for teachers and students in grade IV SD / MI.